Older Adults' Experiences of Community Mobility in an Indian Metropolis: A Qualitative Study. (3rd July 2018) - Ramachandran, Meena; Dsouza, Sebestina Anita
Abstract: Aims: This study aimed to explore and understand how older adults experience community mobility within an urban Indian context, using a phenomenological approach. Methods: Ten older adults residing in Chennai city participated in this study. The investigator conducted individual, in-depth interviews of 60–75 minutes each. Results: Participants placed high value on community mobility, which contributed to their occupational participation and well-being. Participants identified numerous physical, social and attitudinal barriers to community mobility in their environment, leading to fear and restrictions in community mobility. Conclusion: The study findings underscore the need for the development of age-friendly communities within Indian society to promote occupational justice for older adults. Occupational therapists in India can intervene at the government, community, family and individual levels to enable older adults' community mobility and occupational participation. Future research to investigate context-specific interventions to facilitate older adults' community mobility is recommended.